"The determinant of intention behavioral to consume halal food among consumer in Klang Valley" / Noor Raihanum Naif (Faculty of Business and Management, 2007)
This study is conducting to identify the determinants that will lead to the Muslim consumer consume the Halal food such as meat, dairy product, and others in Klang Valley, Malaysia. for this study, it is to focusing what the element will be influencing the consumer during purchasing the Halal food. It is because, the purchasing process not only influencing by the economics and nutrition needs factors, however it also relating to the social and culture factors. The purpose of this study is to identify the relationship between the intention behavioral with tile attitude, subject of norms, perceived behavioral control end habits which are constructing by Theory Planned Behavior (TPB). A sample of 91 respondents took part in this research. This study is using three method analysis which are frequency analysis, chi square test and correlation. The population of this study included all the Muslim consumer of Klang Valley. There is only one approach in collecting data which is primary data by using personal administered questionnaire. The questionnaire are distributing to three hypermarkets which are Tesco in Puchong, Giant in Shah Alam and Kelana Jaya within two weeks in August 2007. The analysis of the responses by respondents revealed a certain determinants of the consumer behavior towards the consuming Halal food. The research presents the finding study on the research question and hypotheses.